PRMT6 promotes colorectal cancer progress via activating MYC signaling - Xin Zhang; Mingxin Jin; Yali Chu; Fengjun Liu; Hui Qu; Cheng Chen (Journal of Translational Medicine)
Abstract Colorectal cancer (CRC) remains a major global health challenge, with high rates of incidence and mortality. This study investigates the role of protein arginine methyltransferase 6 (PRMT6) as an oncogene in CRC and its mechanistic involvement in tumor progression. We found that PRMT6 is significantly overexpressed in CRC tissues compared to adjacent normal tissues and is associated with poorer patient survival. Functional assays demonstrated that PRMT6 promotes CRC cell proliferation, migration, and invasion. Mechanistically, PRMT6 enhances MYC signaling by stabilizing c-MYC through mono-methylation at arginine 371, which inhibits c-MYC poly-ubiquitination and subsequent degradation. This post-translational modification is crucial for PRMT6-induced cancer cell proliferation. Xenograft models further validated that PRMT6 knockdown results in reduced tumor growth and decreased c-MYC levels. Our findings highlight PRMT6 as a key regulator of c-MYC stability and CRC progression, suggesting that targeting PRMT6 or its effects on c-MYC could offer a promising strategy for CRC treatment.